No Differences in Wound Healing and Scar Formation Were Observed in Patients With Different COVID-19 Vaccination Intervals - Dong, Chen; Yu, Zhou; Quan, Xin; Wei, Siming; Wang, Jiayang; Ma, Xianjie (Frontiers in Public Health, 2022)
Background: Safety concerns are one of the most common reasons for COVID-19 vaccination refusal. In the field of plastic and reconstructive surgery, whether COVID-19 vaccination influences wound healing and scar formation is worthy of special attention. Methods: In this study, adult trauma patients with subcutaneous suture placed by a single plastic surgeon in a single center were included. The vaccination interval was defined as the interval between the last dose of COVID-19 vaccine and when surgical sutures were introduced. The patients were categorized by vaccination interval into three groups of <1 month, 1–3 months, and ≥3 months. Wound healing and scar formation were rated according to the Wound Assessment Inventory (WAI) and Patient and Observer Scar Assessment Scale (POSAS) in the groups at 7 days and after a 3-month follow-up. Results: All total and individual scores of WAI and POSAS were not significantly different among the groups. Conclusion: No differences in wound healing and scar formation were observed in patients with different COVID-19 vaccination intervals. Thus, it is not necessary to postpone COVID-19 vaccination, as the vaccine does not affect wound healing and scar formation in patients undergoing surgery. This study aimed to eliminate concerns and hesitancy in receiving the COVID-19 vaccine.